Engineering hybrid textile braids for tendon and ligament repair application. Issue 17 (13th December 2021) - Peixoto, Tânia; Carneiro, Sofia; Fangueiro, Raúl; Guedes, Rui M.; Paiva, Maria C.; Lopes, Maria A.
Abstract: Challenges involving tendon and ligament repair have motivated the investigation of new strategies to improve clinical outcomes. These have been mainly based on polymer constructs, which may be non‐biodegradable or biodegradable. The former typically fails due to lack of device integration and the latter demands a complex balance between biodegradability and tissue ingrowth, often failing due to insufficient mechanical properties. This work presents the development of hybrid braids based on polyethylene terephthalate (PET) and polylactic acid (PLA) yarns. A textile technique was used to fabricate braids based on 16 multifilament yarns of varying PLA/PET composition. The composition was varied to maximize biodegradability while ensuring mechanical performance. The braids' morphology, physical and mechanical properties were characterized. As production parameters and architecture were maintained, the braids exhibited similar porosity and wicking ability. The breaking force and stiffness decreased significantly as the number of PLA yarns increased, although strain levels remained constant. Braids containing 10 and 12 PET yarns (out of the total 16 yarns) demonstrated good creep and force‐relaxation behavior, as well as resistance to cyclic loading. These compositions were selected for future work, to be assembled into more elaborate structures to mimic the fibrous organization and tensile properties of different tendons/ligaments. Abstract :